Self-reported urinary incontinence in the postpartum period: clinical characteristics - Lopes, Daniela Biguetti Martins; Praça, Neide de Souza (Revista da Escola de Enfermagem da USP, 2012)
The objective of this cross-sectional study was to characterize the manifestations of self-reported urinary incontinence in the postpartum period. We interviewed 288 women who were clients of a teaching health center in São Paulo, between the months of January and August of 2009. The data showed that among the 71 incontinent women (24.6%), 44 (62%) reported stress urinary incontinence, 65 (91.5%) were aware of urine leakage, 33 women (46.5%) experienced urine loss more than once a week, and 24 (33.8%) reported persistent urinary incontinence at the time of interview. The severity classified as moderate urinary incontinence was identified in 53 women (74.7%). The findings highlight the importance of studies on urinary incontinence in the postpartum period, as well as approaching this issue in education and health care interventions with women in the reproductive stage.